1959
DOI: 10.1021/ja01533a012
|View full text |Cite
|
Sign up to set email alerts
|

A Reversible Dropping Gallium Amalgam Electrode

Abstract: the positions of several anomalous spectral lines. In 1875 de Boisbaudran^ reported the actual separation of a small quantity of the element. Its physical properties were found to be very close to those predicted by Mendel eeff. The new element was named after the country in which it was discovered-Gaul (France). Gallium is dis-3 6 tributed widely, * although in very small amounts (never (6) E. Einecke, "Das Gallium," Leipzig, Verlag von Leopold Voss, 1937. more than 0 .01$ in any material) over the whole of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1968
1968
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 3 publications
3
26
0
Order By: Relevance
“…The diffusion coefficient values of Ga"' that we obtained are twice the value of 0.84 x cm2/s, that MacNevin and Moorhead [4] reported for Gal* in 7.5M KSCN, and half the value of 5 . 5 6~ lop6 cm2/s given by Sagadieva [17] for Ga metal in mercury.…”
Section: Diffusion Coefficientssupporting
confidence: 49%
See 1 more Smart Citation
“…The diffusion coefficient values of Ga"' that we obtained are twice the value of 0.84 x cm2/s, that MacNevin and Moorhead [4] reported for Gal* in 7.5M KSCN, and half the value of 5 . 5 6~ lop6 cm2/s given by Sagadieva [17] for Ga metal in mercury.…”
Section: Diffusion Coefficientssupporting
confidence: 49%
“…Challenger also reported half-wave potentials for gallium in KNO3 and KCl as -1.05 V and -1.1 V (vs. SCE), respectively. MacNevin and Moorhead [4] have reported polarographic irreversibility for gallium in KN03 solutions. However, the authors observed reversibility for the gallium in 7.5 M KSCN.…”
Section: Introductionmentioning
confidence: 99%
“…15,16) Liquid gallium can be used as dropping electrode. The overpotential measurements pertaining to the hydrogen electrode reaction (HER) on liquid gallium has been conducted in acidic and alkaline media and in the presence of alkali metal.…”
Section: )mentioning
confidence: 99%
“…However, reversible gallium reduction was attained by the addition of 46) or halide 47) as well as SC 15,16) to the solution and by elevated temperature. (Fig.…”
Section: Yonghwa Chung and Chi-woo Leementioning
confidence: 99%
See 1 more Smart Citation